Farsighted miners under transaction fee mechanism EIP1559 - Jens Leth Hougaard; Mohsen Pourpouneh (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2022)
We investigate the recent fee mechanism EIP1559 of the Ethereum network. Whereas previous studies have focused on myopic miners, we here focus on strategic miners in the sense of miners being able to reason k-blocks ahead. We derive expressions for optimal miner behavior (in terms of setting block sizes) in the case of 2-block foresight and varying degrees of hashing power. Results indicate that a sufficiently large mining pool will have enough hashing power to gain by strategic foresight. We further use a simulation study to examine the impact of both 2-block and 3-block foresight. In particular, the simulation study indicates that for realistic levels of hashing power, mining pools do not gain from the being able to reason more than 2 blocks ahead. Moreover, even though the presence of strategic miners increase the variation in block sizes and potentially empty blocks, overall system throughput tend to increase slightly compared to myopic mining.
Keywords: D47; D53; L11; L17; 330; Blockchain; Ethereum; Transaction fee mechanism